(untitled) (Journal of Parents and Teachers, 2014)
The Christmas holidays are approaching, and with them, an increase in leisure time. And why not take advantage of it to cook and explore the world of food? The fact that children cook gives them many advantages, including increased creativity, increased patience and self-control, the incorporation of many healthy eating habits, and fun.